Post-pandemic influenza-associated mortality in Mexico. (17th February 2019) - Salto-Quintana, Jack N.; Rivera-Alfaro, Gerardo; Sánchez-Ramos, Evelyn L.; Gómez-Gómez, Alejandro; Noyola, Daniel E.
ABSTRACT: Influenza is a leading cause of respiratory tract infections worldwide and there is limited information on the impact of the influenza A(H1N1)pdm virus on mortality after the 2009 pandemic. Using national mortality register data through 1998–2015 in Mexico, influenza-associated mortality was estimated for respiratory, cardiovascular, and all-cause events. The proportion of influenza-associated respiratory and cardiovascular deaths among different age groups were compared. There were 8, 853, 986 death registries included for the 1998–2015 winter seasons, average influenza-associated respiratory, cardiovascular, and all-cause mortality rates were 5.2, 6.3, and 19.6 deaths/100, 000 population, respectively. The largest number of respiratory influenza-associated deaths occurred in adults 60 years of age and older, followed by children <5 years of age; during the 2009 pandemic, 2011–2012, and 2013–2014 winter seasons there was a larger number of deaths in the 20–59 years old group. Influenza-associated mortality rates showed a continuous reduction in children <5 years of age. After the 2009 pandemic, influenza A(H1N1)pdm09 virus-associated mortality in Mexico showed a persistent change in the demographic pattern of the most severely affected population, particularly during the 2013–2014 season. Influenza associated-mortality has decreased in children <5 years of age and continue to be elevated in adults >60 years of age.